Deformation-Tailored MoS2 Optoelectronics: Fold-Induced Band Reconstruction for Programmable Polarity Switching - Bo Zhang; Yaqian Liu; Zhen Chen; Xiaofang Wang (Nanomaterials)
This study proposes an innovative design strategy for molybdenum disulfide (MoS2) optoelectronic devices based on three-dimensional folded configurations. A “Z”-shaped folded MoS2 device was fabricated through mechanical exfoliation combined with a pre-strain technique on elastic substrates. Experimental investigations reveal that the geometric folding deformation induces novel photocurrent response zones near folded regions beyond the Schottky junction area via band structure reconstruction, achieving triple polarity switching (negative–positive–negative–positive) of photocurrent. This breakthrough overcomes the single-polarity separation mechanism limitation in conventional planar devices. Scanning photocurrent microscopy demonstrates a 40-fold enhancement in photocurrent intensity at folded regions compared to flat areas, attributed to the optimization of carrier separation efficiency through a pn junction-like built-in electric field induced by the three-dimensional configuration. Voltage-modulation experiments show that negative bias (−150 mV) expands positive response regions, while +200 mV bias induces a global negative response, revealing a dynamic synergy between folding deformation and electric field regulation. Theoretical analysis identifies that the band bending and built-in electric field in folded regions constitutes the physical origin of multiple polarity reversals. This work establishes a design paradigm integrating “geometric deformation-band engineering” for regulating optoelectronic properties of two-dimensional materials, demonstrating significant application potential in programmable photoelectric sensing and neuromorphic devices.